2010 14th European Conference on Software Maintenance and Reengineering 2010
DOI: 10.1109/csmr.2010.48
|View full text |Cite
|
Sign up to set email alerts
|

The Hybrid Technique for Object-Oriented Software Change Impact Analysis

Abstract: Change impact analysis techniques that underestimate impact may cause important financial losses from the point of view of an IT services company. Thus, reducing falsenegatives in these techniques is a goal with strong practical relevance. This work presents a technique that uses both static and dynamic analysis of object-oriented source code to improve resulting impact estimates in terms of recall. The technique consists of three steps: static analysis to identify structural dependencies between code entities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Similar to the work of Huang and Song [113], [114], Maia et al [116] propose a new approach to combine static and dynamic impact analysis to improve the detection of impacted entities, and to reduce the number of falsepositives. The approach combines execution after sequences with the analysis of program dependencies for impact prediction.…”
Section: ) Execution Tracesmentioning
confidence: 99%
“…Similar to the work of Huang and Song [113], [114], Maia et al [116] propose a new approach to combine static and dynamic impact analysis to improve the detection of impacted entities, and to reduce the number of falsepositives. The approach combines execution after sequences with the analysis of program dependencies for impact prediction.…”
Section: ) Execution Tracesmentioning
confidence: 99%
“…Previous studies have shown that none of them achieved significant precision gain over PI/EAS [7], [28]. SD-IMPALA [29] also explored hybrid DDIA yet it focuses on improving the recall of DDIA and does that at the cost of penalizing precision. It uses call graphs as the static dependence model and is shown even less precise than its predecessor Impala [30] and PI/EAS.…”
Section: Threats To Validitymentioning
confidence: 96%
“…impact distance, and stop searching if it reaches a certain depth. This technique used in [18] based on a (weak) assumption that if direct impacts have high potential for being true, then those further away will be less likely. Future work would involve investigating other techniques that can be employed to improve our current algorithms.…”
Section: Where N Is the Number Of Intra-agent Dgs (Ie The Sub-graphmentioning
confidence: 99%
“…Precision and recall are the most widely-used metrics in the information retrieval literature and have been recently adapted to the impact analysis setting (e.g. [18]). Precision is defined as the fraction of the estimated impacted entities (i.e.…”
Section: B Experimentsmentioning
confidence: 99%